Analisis Kebutuhan Kompetensi Lulusan Akuntansi - Dwiharyadi, Anda; Asrina, Novi; Rosalina, Eka (Akuntansi dan Manajemen, 2021)
In accordance with the demands of the times in today's digital era resulting in the industry looking for skilled human resources in their fields. Job seekers are required to have the skills expected by the industry in order to compete for the expected job positions. For that it is important for job seekers to equip themselves with skills that are the needs of the industry. Skill improvement needs support from educational institutions in creating skilled human resources in accordance with the qualifications required by the industry. This study aims to identify what is needed from an accounting graduate. This research was conducted with descriptive quantitative method, with content analysis approach. By using the incidental sampling technique, 705 industrial job vacancies were published on the online job vacancy website for the period January 2021 to June 2021. This study focuses on accounting work including financial accountants, auditors, and tax accountants. The results showed that the basic technical skills of accounting (Technical Skills) which include basic understanding of accounting, mastery of accounting software and Microsoft office are the skills most needed by the world of work. Meanwhile, the generic skills needed by the industry are communication skills, which are derived skills from interpersonal skills.